Auctions of the wood on the stump in PE "Srbijašume" - Keča Ljiljana; Sinđelić Marko; Marčeta Milica; Pajić Sanja (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2017)
Forest assortments can be sold in two ways: “on the stump” (in the standing state) and in the form of forest timber assortments. The paper analyzes auctions of wood “on the stump”, during the first half of 2016, realized within PE “Srbijašume”. The research is based on secondary data, generated from the PE Srbijašume reports. These includes data relating to: quantities of wood, initial bidding and auctioned prices, bidding effects, number of bidders on bids and a price list for a analzyed year. FE “Šumarstvo” from Raška had the most auctions with 46 bids held. Of the total of 14 forest estates that conducted auctions, half had more than 50% of successfully implemented parties, two estates had exactly 50%, and five estates had less than 50%. FE “Niš” has the highest income from auctions of wood in the standing state, which amounts to 26.082.926 dinars. Only FE from Užice and FE from Prokuplje had a bidding effect of over 10%. The highest number of bids, as much as 70, was announced in March. Most of the lots entered the sixth category by size, i.e. the category where the wood volume ranged from 300 to 500 m3. Forest estates during the sale of the tree on the stump were mostly sold by wood of hardwoods. On the basis of the analyzed data, the existence of linear dependence between the initial and the auctioned price was determined.